2019
DOI: 10.1002/hbm.24681
|View full text |Cite
|
Sign up to set email alerts
|

The role of the cerebellum in adaptation: ALE meta‐analyses on sensory feedback error

Abstract: It is widely accepted that unexpected sensory consequences of self‐action engage the cerebellum. However, we currently lack consensus on where in the cerebellum, we find fine‐grained differentiation to unexpected sensory feedback. This may result from methodological diversity in task‐based human neuroimaging studies that experimentally alter the quality of self‐generated sensory feedback. We gathered existing studies that manipulated sensory feedback using a variety of methodological approaches and performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 167 publications
3
36
0
Order By: Relevance
“…As expected, we found pSTG to provide a significant error signal to the first presentations of the delayed sound conditions that adapted over the course of repeated presentations in the trial blocks (Hypothesis 4). This is in line with studies regarding pSTG as an auditory error detector responding to altered feedback (Fu et al, 2006;Zheng et al, 2010;Johnson et al, 2019). In one of our previous behavioral studies, we presented delayed auditory feedback during the actual performance of hurdling (Kennel et al, 2015) and found an interfering effect on the first hurdling trial, whereas performance restored to normal in subsequent trials.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As expected, we found pSTG to provide a significant error signal to the first presentations of the delayed sound conditions that adapted over the course of repeated presentations in the trial blocks (Hypothesis 4). This is in line with studies regarding pSTG as an auditory error detector responding to altered feedback (Fu et al, 2006;Zheng et al, 2010;Johnson et al, 2019). In one of our previous behavioral studies, we presented delayed auditory feedback during the actual performance of hurdling (Kennel et al, 2015) and found an interfering effect on the first hurdling trial, whereas performance restored to normal in subsequent trials.…”
Section: Discussionsupporting
confidence: 90%
“…SMA hence seems not immediately involved in detecting altered feedback, in contrast to pSTG and pCC, but rather provides additional top–down information about the intended action outcome whenever perceived outcome differs from the expected. Being critical for audio–motor associations ( Lima et al, 2016 ; Johnson et al, 2019 ), the SMA might get engaged when auditory delays persist over a longer time to modify audio–motor models or to amplify other modalities for motor control. Accordingly, pSTG and SMA beta values also tended to be correlated in the delayed conditions, but not in the undelayed conditions (Hypothesis 6).…”
Section: Discussionmentioning
confidence: 99%
“…The localization of the right IFG ROI in the current study was determined by an ALE meta-analysis on neuroimaging studies that experimentally manipulated auditory feedback from both vocal and manual production (Johnson et al, 2019). As the current experimental design required no explicit response to a change in stimulus quality, we hypothesized that increased activity in the right IFG pars opercularis may represent the initial salience response to unexpected voice quality.…”
Section: Expected Feedback and The Ifgmentioning
confidence: 99%
“…In addition to auditory cortex, activation in the right inferior frontal gyrus increases in response to distorted auditory feedback (Johnson et al, 2019). However, while attenuation of the right aSTG activation reflects expected stimulus quality, the right IFG is selectively responsive to unexpected sensory events (Aron, Robbins, & Poldrack, 2004).…”
mentioning
confidence: 99%
“…It can enable cognitive, affective and behavioural adaptation across diverse environmental contexts (Sokolov, Miall, & Ivry, 2017;Spampinato & Celnik, 2018). It has been proposed that the cerebellum is a key region in the formation of internal models representing how organisms interact with their environment (Ito, 2008; General factors and the cerebellum 47 Belyk, Schwartze, Pinheiro, & Kotz, 2019;Raymond & Medina, 2018;Wolpert, Miall, & Kawato, 1998). A functioning cerebellum can enable the generalisation of these internal models of behaviour to new contexts in so called context-response linkage (Thach, 1997).…”
Section: Part 3: Synthesismentioning
confidence: 99%